Efektivitas Model Pembelajaran LSQ terhadap Hasil Belajar PKn Peserta Didik Kelas IV SD Negeri 31 Pulau Samatellu Lompo Kab. Pangkep - Rindiani; Usman; M Mirza fatahullah (Prodi PGMI IAI Sahid, 2023)
This research aims to describe (1) the implementation of the Learning Start With A Question learning model through the subject of Civics Education in grade IV of State Elementary School 31 Pulau Samatellu Lompo, Pangkep Regency, (2) the learning outcomes of Civics Education for grade IV students of State Elementary School 31 Pulau Samatellu Lompo, Pangkep Regency before and after the implementation of the Learning Start With A Question model, and (3) to analyze the effectiveness of the Learning Start With A Question model in teaching Civics Education towards the learning outcomes of grade IV students of State Elementary School 31 Pulau Samatellu, Pangkep Regency.The research design used in this study was a pre-experimental design with a